The importance of facilitating strategies in dental treatment in patients with Autism Spectrum Disorder (ASD) (Research, Society and Development, 2023)
Introduction: It is essential to constantly search for alternatives that accommodate autistic patients, applying strategies that help in communicating with them, considering verbal, non-verbal, illustrative and sensory methods. Objectives: the main objective of this work is to highlight the importance of using facilitating strategies in dental treatment for patients with ASD, through a literature review, optimizing the quality of care for people on the autism spectrum, and educating professionals and parents. Materials and Methods: It is based on a bibliographical research of the integrative literature review type on the use of techniques and strategies to facilitate dental care for autistic patients. Literature review: it is reported that some techniques make consultation even easier, they are called basic and advanced. Considering as basic, those that involve non-verbal communication, distractions, offering rewards. The advanced ones include general anesthesia, a very effective alternative to invasive procedures. Conclusion: Each treatment must be individualized, based on your needs, always seeking to fit into the world of the patient with ASD, bringing innovations that reduce discomfort at the time of the consultation.